Prevalence of pelvic floor dysfunction: a Saudi national survey - Ahmed Al-Badr; Zarqa Saleem; Ouhoud Kaddour; Bader Almosaieed; Ashraf Dawood; Mohamad Al-Tannir; Faisal AlTurki; Reem Alharbi; Nasser Alsanea (BMC, 2022)
Abstract Background Pelvic Floor Dysfunction (PFD) is a global health problem affecting millions of women worldwide and comprises a broad range of clinical dysfunctions such as urinary incontinence (UI), fecal incontinence (FI), pelvic organ prolapse (POP) vaginal laxity (VL), vaginal wind (VW), and overactive bladder (OAB). This study aims to estimate the prevalence of PFD among Saudi women attending primary health care centers (PHCCs) across 13 regions of Saudi Arabia and their characteristics along with associated factors. Methods A cross-sectional study was conducted on 2,289 non-pregnant women. The probability population proportional sampling technique was employed followed by a convenient sampling technique to recruit eligible women. Types of PFD were assessed using a self-administered electronic questionnaire. Pelvic Floor Distress Index (PFDI-20) was used to assess the primary study outcomes (FI, VL, POP, VW, and OAB). A multivariate logistic regression model was used to identify independent associated factors for PFD. Results The findings showed that 830 women (36.3%) had any type of UI. Stress UI affected726 (31.7%) women, whilst 525 women (22.9%) had urge UI. VL occurred in 505 women (22.1%), whilst POP occurred in 536 women (23.4%). VW occurred in 733 participants and (32%) 1238 women (54.1%) had OAB. The multivariate analysis suggested that region, location, parity, and assisted birth were significantly associated with UI, VL, FI and PFD (P < 0.001). Conclusion PFD is a common condition among Saudi women. UI, VL, VW, OAB, POP and FI increased consistently among urban women with increased age, greater parity, assisted birth, and post-menopausal status.